5-Amino-2,4,6-triiodoisophthalic acid–4,4′-bipyridine N,N′-dioxide–water (1/1/1) - Zhang, Kou-Lin (International Union of Crystallography, 2011)
The aromatic rings of the N,N′-dioxide molecule in the title compound, C(8)H(4)NI(3)O(4)·C(10)H(8)N(2)O(2)·H(2)O, are twisted by 14.0 (2)°. The –CO(2)H substituents of the 5-amino-2,4,6-triiodoisophthalic acid are twisted by 83.0 (2) and 86.5 (2)° out of the plane of the aromatic ring. In the crystal, the three components are linked by O—H⋯O hydrogen bonds into a three-dimensional network. An N—H⋯O interaction also occurs. One of the amino H atom is not involved in hydrogen bonding.